Cost effects of nurse led triage at an emergency department with the advice to consult the adjacent general practice cooperative for low-risk patients, a cluster randomised trial. Issue 10 (October 2022) - Morreel, Stefan; Homburg, Ines; Philips, Hilde; De Graeve, Diana; Monsieurs, Koenraad G.; Meysman, Jasmine; Lefevere, Eva; Verhoeven, Veronique
Highlights: First randomised cost effects study about diverting ED patients to primary care. Total costs increased 3% (€3.3) by the intervention. Costs decreased 8% (€2.2) for the patient and increased 6% (€5.5) for the insurance. Primary care revenues increased 13%; no reduction found for the emergency department. A financial evaluation is necessary for each healthcare system considering extended triage. Abstract: Background: During the TRIAGE trial, emergency nurses diverted 13.3% of patients with low-risk complaints from a Belgian emergency department (ED) to the adjacent general practitioner cooperative (GPC). We examined the effects of this diversion on the total cost, insurance costs and patient costs, as charged on the invoice. Changes in the cost composition and the direct impact on revenues of both locations were examined as a secondary objective. Methods: The differences in costs between intervention and control weekends were tested with two-sample t-tests and Kolmogorov-Smirnov (KS) tests. For the main outcomes an additional generalised linear model was created. Proportions of patients charged with certain costs were examined using Pearson's chi-square tests. Average revenues per weekend were compared using pooled t-tests. Results: During intervention weekends, total costs increased by 3% (€3.3). The costs decreased by 8% (€2.2) for patients and increased by 6% (€5.5) for insurance, mainly driven by differences in physician fees. More patients were charged a consultation fee only (25% vs. 19%, p-value<0.01). The GPC's revenues increased by 13% (p-value=0.06); no change was found for the ED's revenues. Conclusion: The intervention reduced costs slightly for patients, while total costs and insurance costs slightly increased. When implementing triage systems with primary care involvement, the effects on the costs and revenues of the stakeholders should be monitored. Graphical abstract: Image, graphical abstract